Comparison of pharmacopuncture, aquapuncture and acepromazine for sedation of horses - Luna, Stélio Pacca Loureiro [UNESP]; Angeli, Ana L. [UNESP]; Ferreira, Cristiane L. [UNESP]; Lettry, Vivien [UNESP]; Scognamillo-Szabo, Marcia (Oxford University Press, 2008)
Pharmacopuncture, the injection of subclinical doses of drugs into acupoints reduces drug undesirable side effects, residues in animal consumption products and treatment costs in large animals. Acepromazine (Acp) produces several undesirable effects, such as hypotension. Previous studies with the injection of 1/10 of Acp dose in dog acupoints showed its advantage for sedation, minimizing undesirable effects. Eight horses were randomly submitted to four different treatment protocols according to a Latin Square double-blind design: (i) 0.1 ml kg(1) of saline subcutaneously injected at the cervical region, (ii) 0.1 mg kg(1) of Acp injected subcutaneously at the cervical region, (iii) 0.01 ml kg(1) of saline injected into GV1 acupoint (aquapuncture) and (iv) 0.01 mg kg(1) of Acp injected into GV1 acupoint (pharmacopuncture). Heart rate, respiratory rate, head height and degree of sedation were measured before and at 30, 60 and 90 min after treatments. Signs of sedation were observed in all treated groups at 30 min and only in 1/10Acp-GV1 at 60 min after the treatments. Only the group treated with 0.1 mg kg(1) of Acp s.c. had significantly lower values of head height at 30 min. Respiratory rate tended to reduce in all groups but was significantly lower only in horses treated with 0.1 mg kg(1) of Acp s.c. Heart rate remained unchanged in all groups. Acp-pharmacopuncture on GV1 in horses produced a mild sedation when compared with the conventional dose of Acp. More investigations are necessary to determine the optimal dosage of Acp-pharmacopuncture for sedation in horses.
Keywords: acupoint; acupuncture; equine; injection; sedation